Crime Prevention Strategies in Tourist Destinations (A Study of the Ujil River Baths, Kampar Regency) - Ramadhan, Muhammad Putra; Askarial (Sisi Lain Realita, 2025)
This study aims to examine the role of the Social Service for Women's Empowerment and Child Protection in Rokan Hulu Regency in reducing early marriage, as well as to identify forms of crime occurring at the Ujil River Bathing tourism site and analyze prevention strategies using the Situational Crime Prevention approach. The research employs a descriptive qualitative method with in-depth interviews as the primary data collection technique. Findings indicate that early marriage is mitigated through education, advocacy, and cross-sectoral collaboration. Meanwhile, the most prevalent form of crime at the Ujil River Bathing site is non-verbal misconduct, particularly covert photo-taking without consent, often occurring in poorly monitored areas. Prevention strategies include enhancing physical and social surveillance, increasing the risk of apprehension through rapid reporting mechanisms and personnel presence, reducing offender rewards through direct intervention and rule enforcement, and fostering ethical awareness through social norm education. Community members also play a role as informal guardians by actively participating in maintaining a safe environment. In conclusion, strengthening social sensitivity, collaborative monitoring, and victim-friendly reporting systems are essential foundations for creating safe and inclusive public spaces free from sexual violence.